Clostridium difficile in an Urban, University-Affiliated Long-Term Acute-Care Hospital. (7th December 2016) - Jacob, Jerry; Wu, Jingwei; Han, Jennifer; Nelson, Deborah B.
Abstract : OBJECTIVES: To describe the characteristics and impact of Clostridium difficile infection (CDI) in a long-term acute-care hospital (LTACH). DESIGN: Retrospective matched cohort study. SETTING: A 38-bed, urban, university-affiliated LTACH. METHODS: The characteristics of LTACH-onset CDI were assessed among patients hospitalized between July 2008 and October 2015. Patients with CDI were matched to concurrently hospitalized patients without a diagnosis of CDI. Severe CDI was defined as CDI with 2 or more of the following criteria: age ≥65 years, serum creatinine ≥2 mg/dL, or peripheral leukocyte count ≥20, 000 cells/μL. A conditional Poisson regression model was developed to determine characteristics associated with a composite primary outcome of 30-day readmission to an acute-care hospital, or mortality. RESULTS: The overall incidence of CDI was 21.4 cases per 10, 000 patient days, with 27% of infections classified as severe. Patients with CDI had a mean age of 70 years (SD, 14 years), a mean Charlson comorbidity index of 3.6 (SD, 2.0), a median length of stay of 33 days (interquartile range [IQR], 24–45 days), and a median time between admission and CDI diagnosis of 16 days (IQR, 9–23 days). The most commonly prescribed antibiotic preceding a CDI diagnosis was a cephalosporin, with median duration of 8 days (IQR, 4–14 days). In multivariate analysis, CDI was not significantly associated with the primary outcome (relative risk, 0.97; 95% CI, 0.59–1.58). CONCLUSIONS: Incidence of CDI in an urban, university-affiliated LTACH was high. Future research should focus on infection prevention measures to decrease the burden of CDI in this complex patient population. Infect Control Hosp Epidemiol 2017;38:294–299